2002
DOI: 10.1016/s0960-9822(02)00807-2
|View full text |Cite
|
Sign up to set email alerts
|

Arp2/3-Dependent Psuedocleavage Furrow Assembly in Syncytial Drosophila Embryos

Abstract: The Drosophila Arp2/3 complex and Scrambled protein are required for actin cap expansion and pseudocleavage furrow formation during the syncytial blastoderm divisions. We propose that Scrambled-dependent localization of Arp2/3 to the margins of the expanding caps triggers local actin polymerization that drives cap expansion and pseudocleavage furrow assembly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
109
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(114 citation statements)
references
References 32 publications
5
109
0
Order By: Relevance
“…In syncytial embryos, Arp3 is enriched in the vicinity of actin structures, but is not restricted to these locations (Stevenson et al, 2002). Its localization later in embryogenesis was not previously reported.…”
Section: The Localization Of Cytoskeletal Regulatorsmentioning
confidence: 78%
See 1 more Smart Citation
“…In syncytial embryos, Arp3 is enriched in the vicinity of actin structures, but is not restricted to these locations (Stevenson et al, 2002). Its localization later in embryogenesis was not previously reported.…”
Section: The Localization Of Cytoskeletal Regulatorsmentioning
confidence: 78%
“…To test this hypothesis, genetic analyses will be necessary. This presents significant obstacles, as Arp2/3 (Stevenson et al, 2002) and Dia (Afshar et al, 2000) are required for much earlier events (syncytial stages and cellularization), while maternal Ena plays a role in oogenesis (J. Gates, J. P. Mahaffey and M.P., unpublished data), complicating analysis of loss-of-function mutants.…”
Section: Journal Of Cell Science 119 (3)mentioning
confidence: 99%
“…Scar has been shown to be required for axon development, egg chamber structure, adult eye morphology (Zallen et al, 2002) and myoblast fusion (Berger et al, 2008); Wasp has been demonstrated to be required for Notchmediated cell-fate decisions (Ben-Yaacov et al, 2001), rhabdomere microvilli formation (Zelhof and Hardy, 2004), bristle development (Bogdan et al, 2004;Bogdan et al, 2005;Tal et al, 2002) and myoblast fusion (Berger et al, 2008;Schafer et al, 2007); and Wash is required for pupal development (Linardopoulou et al, 2007) and oogenesis, as described in this study. Mutants in various subunits of Arp2/3 have also been described, offering additional insight into how Wash, Wasp and Scar shape the cytoskeleton during development Stevenson et al, 2002). Interestingly, the spectrum of Arp2/3 mutant phenotypes reported does not completely overlap with all of the phenotypes associated with these WAS family mutants.…”
Section: Wash Function In Drosophila Oogenesismentioning
confidence: 99%
“…In complex multicellular organisms, the biological function of the Arp2/3 complex has been studied only in fruitfly (Drosophila melanogaster). A mutation of one Arp2/3 complex subunit, ARPC1, causes spindle fusion because of pseudocleavage furrow disruption in syncytical fruitfly embryos Stevenson et al, 2002). Arabidopsis, with numerous advantages for genetic studies including the availability of various collections of T-DNA insertion mutants, provides a good model system to study the function of the Arp2/3 complex in higher eukaryotes.…”
mentioning
confidence: 99%